MONOGENEAN PARASITES OF Prochilodus nigricans (CHARACIFORMES: PROCHILODONTIDAE) ARISING FROM NATURAL ENVIRONMENT AND A CULTIVATION POND IN PERUVIAN AMAZON - HIDALGO PIÑA, Lizeth (2017)
In recent years, the Peruvian Amazon has been developing the fish culture of native species of great potential, standing out the "boquichico", Prochilodus nigricans as one of the most promising species. This fish in captivity can be subjected to high levels of stress which can negatively influence its resistance against parasitic infections. Despite its enormous economic importance, little or almost nothing is known about its parasitic fauna. Therefore, the present study aims to identify the branchial monogenoideans parasitizing young specimens of P. nigricansfrom natural environment and a culture pond. Forty gills of P. nigricans from the natural environment and forty from a culture pond were analyzed. The identified monogenoideans were: Apedunculata discoidea, Tereancistrum curimba and T. toksonum. The higher number of individuals were recorded in fish from natural environment. The present study records for the first  time these three parasite species in P. nigricans. The presence of the same monogenoideans in fish from both environments arouses alert to the fish farmers of the region, since under inadequate conditions of cultivation, massive proliferations of these parasites can occur, placing the health and quality of the fish at risk.